Homage to Michel Bornens, who passed away on March 9, 2022 at the age of 84. (10th May 2022) - Goud, Bruno; Azimzadeh, Juliette; Delgehyr, Nathalie; Piel, Matthieu; Thery, Manuel
Abstract : Michel Bornens (1938–2022). Image by Marie‐Berthe Bornens; reproduced with permission.